Use of Prezi Media in Improving Student Learning Outcomes in Social Studies Learning - Mulyana, Eldi; Dahlena, Alni; Septiani, Rina; Nugraha, Fauzi Fiqri; Pratiwi, Asti; Mutaqin, Andre Jaenal (Indonesian Journal of Community Empowerment (IJCE), 2023)
This service was motivated by the decline in participants' learning outcomes in social studies lessons. Teachers only focus on one source of learning books and rarely use learning media. This research aims to determine the use of Prezi Media in improving student learning outcomes in social studies learning. The aim of this service activity is to improve teachers' abilities in using interactive learning media so that it will increase students' learning motivation. The results of this activity have a positive impact on interest in learning and increasing social skills for students. So that through learning activities with interactive and innovative media, teachers can provide skills in providing learning and can improve student learning outcomes. Through the media Prezzi can provide active learning in social studies.